Description of Hematological Parameters and Severity Levels of COVID-19 Patients and Disease Progression at Royal Prima Hospital, Medan, North Sumatera, Indonesia - Azah, Yunita Wannur; Novalinda Ginting, Chrismis; Chiuman, Linda; Ferdinand, Sahna (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: The severity of COVID-19 can be evaluated by checking several routine hematological parameters. Routine hematology examinations have an important role in early detection, diagnosis, disease management and disease progression. This study aims to determine the relationship between hematological parameters and disease progression and severity in COVID-19 patients. Subjects and Method: This was a cross sectional study conducted at Royal Prima Hospital, Medan, North Sumatera, Indonesia, from January to February 2022. A total of 93 patients who had confirmed COVID-19 were selected using a simple random sampling technique according to the inclusion and exclusion criteria. The research was The dependent variables of this research were disease progression and severity of COVID-19 patients. The independent variables are hematological parameters based on hospital medical record data. Data analysis used the Chi-Square test and logistic regression. Results: 75 people (80.6%) COVID-19 sufferers had severe disease. NLR and D-dimer levels were significantly related to disease progression in COVID-19 sufferers (p<0.05). Leukocyte, lymphocyte, NLR, CRP, D-dimer levels are related to the severity of COVID-19 sufferers (p<0.05). Leukocyte levels have the strongest relationship with the severity of COVID-19 with an OR value of 1.798. Conclusion: NLR and D-dimer levels are significantly related to disease progression and leukocyte. Lymphocyte, NLR, CRP, D-dimer levels are related to the severity of COVID-19 sufferers.